Innate Immunomodulatory Activity of Cedrol, a Component of Essential Oils Isolated from Juniperus Species; Molecules; Vol. 26, iss. 24 - Ozek G. Gulmira; Shchepyotkin I. A. Igor Aleksandrovich; Yermagambetova M. Moldir; Ozek T. Temel; Kirpotina L. N. Liliya Nikolaevna; Almerekova Sh. S. Shyryn; Abugalieva S. I. Saule; Khlebnikov A. I. Andrey Ivanovich; Quinn M. T. Mark (2021, 2021)
Title screen